2017
DOI: 10.1360/n972016-00703
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Early Permian radiolarian fauna in the Solon Obo ophiolite belt, Inner Mongolia and its geological significance

Abstract: The discovery of early Permian reef belt in east Kunlun and its significance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…After the intense magmatic activity in the late Early Carboniferous to Early Permian, magmatic activity became progressively weaker in the area, replaced by Middle Permian Zhesi Formation marine facies strata and alternating marine–continental facies to continental facies Late Permian Linxi Formation strata (270–256 Ma, Figure 14d). Sedimentary studies have revealed the presence of Middle Permian radiolarian fossils in the Maodeng, Zhese Obo, and Xar Moron River areas at the north margin of the NCC (Li, Wang et al, ; Shang, ; Wang et al, ), indicating that this area was still in a deep‐sea environment until the Middle Permian. In the Middle Permian, widespread carbonate rocks and mudstones were developed, with platform facies characteristics (Wang et al, ), reflecting a relatively stable sedimentary environment, with the northward subduction of the plate being almost stagnant or relatively slow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the intense magmatic activity in the late Early Carboniferous to Early Permian, magmatic activity became progressively weaker in the area, replaced by Middle Permian Zhesi Formation marine facies strata and alternating marine–continental facies to continental facies Late Permian Linxi Formation strata (270–256 Ma, Figure 14d). Sedimentary studies have revealed the presence of Middle Permian radiolarian fossils in the Maodeng, Zhese Obo, and Xar Moron River areas at the north margin of the NCC (Li, Wang et al, ; Shang, ; Wang et al, ), indicating that this area was still in a deep‐sea environment until the Middle Permian. In the Middle Permian, widespread carbonate rocks and mudstones were developed, with platform facies characteristics (Wang et al, ), reflecting a relatively stable sedimentary environment, with the northward subduction of the plate being almost stagnant or relatively slow.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Fang et al () discovered gastropods in the Permian Zhesi Formation and concluded from the analysis of the sedimentary facies of the strata that they were mainly deposited in a shallow marine and littoral–shallow marine setting rather than in a deep‐sea environment. Another view holds that the subduction of the PAO occurred during the Late Palaeozoic period and that the final collision of the two cratons was complete between the Late Permian to Early Triassic (Chen et al, ; Eizenhöfer et al, ; Li, Wang et al, ; Li, Wilde, Wang, Xiao, & Guo, ; Liu et al, , Liu, Li et al, ; Xiao et al, ; Zhang et al, ). This view is supported by the observations that the Late Carboniferous to Early Permian island arc magmatism occurred widely in the Sonidzuoqi–Xi Ujimqin Banner areas (Chen, Zhao, & Wilde, ; Kang et al, ; Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data are from this study and Sun, Wu, and Gao (), Luo et al (), Zhang, Jian, Liu, and Hou (), Zhang and Jian (). Cao et al (), Wang, Xu, Liu, Zhao, and Jiang (), Wu et al (), Shi et al (), Wang et al (), Dong, Wang, Sha, and Zhang (), Li, Wilde, Wang, Xiao, and Guo (), Li, Wang, et al (), Liu et al (), Wang et al (), Zhu et al (), and Wang et al () [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Discussionmentioning
confidence: 99%
“…The Late Permian‐Middle Triassic magmatism is locally outcropped south of the Solonker suture zone or nearby, and presents a near E–W trending sublinear distribution parallel to the Solonker suture zone. According to geochemical features, these granites show high Sr/Y ratios and low Mg# values, which have affinities with the adakitic rocks and were possibly derived from a thickened lower crust (Wang, Xu, et al, , ; Sun et al, ; Cao et al, ; Zhang, Jian, et al, ; Li, Wang, et al, ; Liu et al, ). Furthermore, S‐type granites also occur coevally in association with the adakitic rocks with high SiO 2 contents and peraluminous minerals (Wu et al, ).…”
Section: Discussionmentioning
confidence: 99%